Xylanase production by Penicillium oxalicum T3.3 using rice straw as substrate for biobleaching of bamboo pulps - Zahari, Nur Idayu (2017)
Recently, xylanase has raised high attention in pulp and paper industry due to their bleach-boosting properties, which assist bleaching process. Xylanase can improve the performance of pulp. It is a hydrolytic enzyme that can degrade the linear polysaccharide beta-1,4-xylan into xylose. Thus, the aims of this research are to select potential xylanase-producing fungi with enhance xylanase production and to evaluate the performance of the xylanase in assisting the biobleaching process of bamboo pulps. Four fungi species namely Penicillium oxalicum T3.3, Aspergillus niger ATCC 6275, Colletotrichum gliosporoides and Pycnoporus sanguineus were screened for xylanase production based on the observation of clear zone formation on Malt Extract Agar (MEA) containing xylan. P. oxalicum T3.3 and A. niger ATCC 6275 showed larger clear zone formation on the agar plate. These fungi were grown in shake flask by submerged fermentation containing rice straw as substrate. P. oxalicum T3.3 showed highest xylanase activity (65.89 U/mL) with lowest carboxymethyl cellulase (CMCase) (1.88 U/mL) and filter paperase (FPase) activity (0.16 U/mL) after 4 days fermentation at 30°C. The cultural conditions for xylanase production by P. oxalicum T3.3 was investigated under various concentration of rice straw, initial pH, temperature, agitation speed, nitrogen sources and additional of surfactants. The best cultural conditions was determined by one-factor-at-a-time method. By optimizing rice straw concentration at 1% (w/v), initial pH at 6, temperature 35°C, agitation speed at 150 rpm, using yeast extract as the nitrogen source, and addition of Tween 80 as surfactant, the highest xylanase production of 79.12 U/mL was obtained. That is 20% improvement compared to that before optimization. The xylanase was found more stable at pH range of 4.0 to 7.0 and temperature from 45°C to 55°C. The enzyme retained 72% and 51% of its activity after incubation for 2 h and 4 h, respectively at 50°C and pH 6. At -80°C, xylanase was still above its half life for 2 weeks. Biobleaching of bamboo pulps with xylanase was most effective at an enzyme dose of 5 U/g oven dried pulp at pH 7 and incubated in water bath at 50°C. Biobleaching process increased paper brightness by 7.51 points at optimum conditions. Results of chemical composition of biobleached bamboo pulps revealed that lignin content reduced by 25% with only slightly reduction of holocellulose and α-cellulose content by 0.5% and 12% compared to chemically bleached bamboo pulp. Thus, cellulase-poor xylanase produced from P. oxalicum T3.3 grown on rice straw has high potential for biobleaching application in pulp and paper industry in terms of technical and biological performance and economical aspects.